2016
DOI: 10.1002/eco.1732
|View full text |Cite
|
Sign up to set email alerts
|

Energy partitioning and its controls over a heterogeneous semi‐arid shrubland ecosystem in the Lake Naivasha Basin, Kenya

Abstract: This paper reports on the energy balance and partitioning analysed from 3-year micrometeorological flux measurements of energy and water fluxes over a heterogeneous semi-arid shrubland ecosystem in Lake Naivasha basin. The measurements enabled the characterization of the seasonal and interannual variability of the energy and water fluxes of the ecosystem covering two wet years (2012 and 2013) and one drought year (2014). On an annual scale, more than 60% of net radiation (Rn) was partitioned as latent (LE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
2
12
0
Order By: Relevance
“…Similar results were observed by Odongo et al (2016) who found that during the dry season, ET was more strongly linked to VPD and G s compared with R n . Similar results were observed by Odongo et al (2016) who found that during the dry season, ET was more strongly linked to VPD and G s compared with R n .…”
Section: Biophysical Controls Of Energy Partitioningsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were observed by Odongo et al (2016) who found that during the dry season, ET was more strongly linked to VPD and G s compared with R n . Similar results were observed by Odongo et al (2016) who found that during the dry season, ET was more strongly linked to VPD and G s compared with R n .…”
Section: Biophysical Controls Of Energy Partitioningsupporting
confidence: 89%
“…The lower values from this study are indicative of the degree of aridity because the average annual rainfall received was 296.4 mm whereas the Benin study area received rainfall >1,000 mm. Similar results were observed by Odongo et al (2016) who found that during the dry season, ET was more strongly linked to VPD and G s compared with R n . Essentially, the trends in the α and Ω were similar (Figure 10a,c).…”
Section: Biophysical Controls Of Energy Partitioningsupporting
confidence: 89%
See 1 more Smart Citation
“…Odongo et al [40] had similar results in the semi-arid ecosystem which suggested that during the dry seasons, drought conditions in combination with highs level of VPD lead to significant decreases in stomatal conductance that eventually limit partitioning of available energy into latent heat flux. However, during the wet season these factors are non-limiting and radiation is the dominant control of energy partitioning.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, higher VPD corresponds to larger latent heat flux, as a positive impact. On the other hand, the VPD will affect the stomatal conductance of vegetation such that a higher VPD can reduce the stomatal conductance and water vapor released from vegetation, resulting in less latent heat flux, as a negative impact [40]. As shown in Figure 6a, even under relatively wet conditions in the semi-arid region, the positive effect of VPD initially dominates.…”
Section: Effects Of Vpd On Energy Partitioningmentioning
confidence: 99%